SIKAP DAN KEPUASAN KONSUMEN RUMAH MAKAN “XXX” LAMONGAN DI BANDAR LAMPUNG - Rinty Azaria; Sudarma Widjaya; Maya Riantini (Lampung University, 2020)
This study aims to explore the consumers’ attitudes and satisfaction toward restaurant. This research is conducted at